Simulasi Dinamik Pengoperasian Kompresor Sentrifugal Multitahap untuk Mengatasi Penurunan Tekanan Sumur Gas - Pratiwi, Meiti; Dwi Savitri, Nike; Ramli, Yusrin; Sasongko, Dwiwahju; Indarto, Antonius (Jurnal Otomasi Kontrol dan Instrumentasi, 2023)
Currently, the utilization of natural gas as an energy source needs to be optimized due to its increasing demand. The utilization of natural gas to produce LNG requires a high-pressure operating system of 1000 psig. The installation of a multistage centrifugal compressor unit is essential to maintain the operating pressure when there is a decrease in the feed gas pressure from natural gas wells. This study aims to predict the performance of the compressor that would be used and optimize the compressor operating conditions to satisfy the specifications of the gas selling pressure. In this study, simulations were conducted on how to maintain the stability of the feed operating pressure in the case of a drop in the gas source pressure from 1000 psig to 200 psig over a period of 15 years. Herein, the gas flow rate under normal conditions is 80 MMSCFD with a gas flow rate variation under surge (minimum) and maximum conditions of 110% × normal flow rate. By using the compressor map prediction curve and Hysys simulation under dynamic conditions, the compressor performance can be analyzed and then used for process requirements in the field.